Dampak Pengalihan PBB-P2 dan BPHTB Terhadap PDRB dan Belanja Modal - Dirgayany Pala’biran; Meyjerd Rombebunga (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
This research aims to evaluate the impact of the diversion of PBB-P2 (Pajak Bumi dan Bangunan Pedesaan dan Perkotaan) and BPHTB (Bea Perolehan Hak Atas Tanah dan Bangunan) into regional tax on PDRB (Produk Domestik Regional Bruto) and Capital Expenditure in Regencies/Cities of Central Java Province. Secondary data is used and collected from Badan Pusat Statistik (BPS) of Central Java Province and Direktorat Jenderal Perimbangan Keuangan (DJPK) of Indonesia. Based on 35 Regencies/Cities in Central Java. This study uses data four years before and four years after the diversion to regional taxes in Regencies/Cities of Central Java Province, the result show that the PDRB and capital expenditure before the diversion is significantly different with the PDRB and capital expenditure after the diversion. It that the diversion improves regional economic and development.